Beyond the Courtroom: Reforming Consumer Dispute Resolution Policies in Indonesia - Rina Arum Prastyanti; Widi Nugrahaningsih; Lahveenya Panchalingam (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
This study analyses the effectiveness of the Consumer Dispute Settlement Agency (Badan Penyelesaian Sengketa Konsumen or BPSK) in Indonesia and formulates a legal reconstruction of consumer dispute resolution through comparative learning from Malaysia. The study highlights structural, normative, and operational constraints affecting BPSK. These issues worsen due to inflexible regulatory frameworks and weak institutional coordination, particularly in the protection of digital consumers. The research employs a qualitative empirical method with a comparative legal approach between Indonesia and Malaysia, complemented by qualitative descriptive analysis. The study indicates that BPSK has not functioned optimally in providing consumer protection due to limitations in its authority, the absence of direct executorial force of its decisions, and the breadth of its functions without adequate enforcement mechanisms. In contrast, the Malaysian Consumer Claims Tribunal, established under the Consumer Protection Act 1999, issues decisions that are final and binding, thereby providing a higher degree of legal certainty. Legal reconstruction is therefore proposed through the strengthening of regulatory provisions within the Consumer Protection Act, particularly Articles 45, 49, 52, 54, and 56, to enhance the effectiveness of consumer protection in Indonesia.